Support Services Provided by a Child and Youth Care Centre (CYCC) to Adolescent Witnesses of Domestic Violence - Shahana Rasool; Suzanne Swart (The Thinker)
Objective: This article presents the results of a case study conducted at a Child and Youth Care Centre (CYCC) in Pretoria, South Africa, on social service practitioners’ (SSP) views of the support services provided by a CYCC to adolescent witnesses of domestic violence. These support services are explored in terms of four inter-dependent levels including the micro, meso, exo and macro levels of the Ecological Theory, as described by Bronfenbrenner (1979). Method: For this study, a qualitative holistic case study design was adopted. This single case study design was chosen as information was gathered from various sources in only one CYCC. Information was triangulated by using various sources of data, that is interviews with SSPs and the children, as well as the policies of the CYCC regarding services offered for children who have witnessed domestic violence. Results: This study revealed that there are no specialised services at the identified CYCC to support adolescent witnesses of domestic violence. The services that are available seem to be generic and aimed at addressing problem behaviours in children and adolescents, rather than providing proactive, therapeutic support to deal with trauma such as witnessing physical and verbal domestic violence in their home of origin.